New agents for thromboprotection - Labberton, L.; Kenne, E.; Renné, T. (Hämostaseologie, 2015)
Blood coagulation is essential for hemostasis, however excessive coagulation can lead to thrombosis. Factor XII starts the intrinsic coagulation pathway and contact-induced factor XII activation provides the mechanistic basis for the diagnostic aPTT clotting assay. Despite its function for fibrin formation in test tubes, patients and animals lacking factor XII have a completely normal hemostasis. The lack of a bleeding tendency observed in factor XII deficiency states is in sharp contrast to deficiencies of other components of the coagulation cascade and factor XII has been considered to have no function for coagulation in vivo. Recently, experimental animal models showed that factor XII is activated by an inorganic polymer, polyphosphate, which is released from procoagulant platelets and that polyphosphate-driven factor XII activation has an essential role in pathologic thrombus formation. Cumulatively, the data suggest to target polyphosphate, factor XII, or its activated form factor XIIa for anticoagulation. As the factor XII pathway specifically contributes to thrombosis but not to hemostasis, interference with this pathway provides a unique opportunity for safe anticoagulation that is not associated with excess bleeding.The review summarizes current knowledge on factor XII functions, activators and inhibitors.
Keywords: Factor XII; contact system; anticoagulants; polyphosphate